Comparative morphology of the avian maxillary bone (os maxillare) based on an examination of macerated juvenile skeletons. (20th July 2018) - Mayr, Gerald
Abstract: For the first time, isolated maxillary bones of juvenile neornithine birds are examined and compared. Contrary to the anatomical terminology currently employed, the avian maxillare exhibits five rather than four processes. In addition to the praemaxillary, jugal, nasal, and maxillopalatine processes, all palaeognathous and many neognathous birds also have a palatine process. The occurrence of these processes is, however, variable across different clades and only few taxa exhibit a pentaradiate maxillare with all five processes. Within Neognathae, a great morphological variability exists in the shape of the maxillopalatine process, which is more easily studied in juvenile individuals, in which the bones of the beak and palate are not co‐ossified. In some Neognathae, a caudally facing recess is situated in the junction of the maxillopalatine and jugal processes, which is likely to be homologous to the pneumatic recess of palaeognathous birds. Several derived morphologies of potential phylogenetic significance for the characterization of neognathous clades are identified and major morphological transformations in the lineage leading towards modern birds are highlighted.